Blood pressure, gallstones, and age at first cholecystectomy in U.S. adults: a cross-sectional study - Yue Zhang; Ruifeng Duan; Xin Chen; Lijuan Wei (BMC Gastroenterology)
Abstract Background Gallstones are a prevalent health issue. Recent studies have revealed that blood pressure (BP) may affect gallstone formation. This study assessed the association between hypertension (HTN) and both the prevalence of gallstones and the age at first cholecystectomy among U.S. adults. Methods Data were extracted from the National Health and Nutrition Examination Survey (NHANES) database from 2017 to 2020. Weighted logistic and linear regression analyses and subgroup analyses were employed to investigate the relationships between HTN, gallstone disease (GD), and age at first cholecystectomy. Additionally, this study employed generalized additive models (GAM) and smooth-fitting curves to delineate the relationships. The two-piecewise linear regression model and logarithmic likelihood ratio test elucidated the inflection point of systolic blood pressure (SBP) on the age at first cholecystectomy. Results The study included 7,532 participants aged over 20 years. Of these, 817 reported a history of cholecystectomy, and 781 reported a history of gallstones. After adjustment for age, gender, race, diabetes, and hypercholesterolemia, HTN was significantly associated with gallstones in individuals aged 48 years (OR = 1.39; 95% CI: 1.03, 1.88). SBP was positively correlated with the age at first cholecystectomy (β = 0.20, 95% CI: 0.13, 0.26). When examining the correlation between SBP and age at surgery, age was first positively and then negatively correlated with BP, with 170 as an inflection point. We carried out subgroup analyses to evaluate the robustness of the link between HTN and cholecystectomy. The results revealed a consistent positive association between HTN and cholecystectomy across these variables (p > 0.05). Conclusion The study found a correlation between BP and the prevalence of gallstones in individuals aged 42 years and older and a positive association between SBP and the age at first cholecystectomy. While causality cannot be confirmed, these findings may assist in identifying early risk groups for GD and early cholecystectomy, thereby enhancing risk stratification and potentially reducing screening costs.